Host Organelle Hijackers: a similar modus operandi for Toxoplasma gondii and Chlamydia trachomatis: co‐infection model as a tool to investigate pathogenesis. Issue 2 (22nd July 2013) - Romano, Julia D.; Coppens, Isabelle
Abstract: The bacterium Chlamydia trachomatis and the protozoan parasite Toxoplasma gondii are the causative agents of chlamydiosis and toxoplasmosis in humans, respectively. Both microorganisms are obligate intracellular pathogens and notorious for extensively modifying the cytoskeletal architecture and the endomembrane system of their host cells to establish productive infections. This review highlights the similar tactics developed by these two pathogens to manipulate their host cell despite their genetic unrelatedness. Using an in vitro cell culture model whereby single fibroblasts are infected by C. trachomatis and T. gondii simultaneously, thus setting up an intracellular competition, we demonstrate that the solutions to the problem of intracellular survival deployed by the parasite and the bacterium may represent an example of convergent evolution, driven by the necessity to acquire nutrients in a hostile environment. Abstract : This mini‐review is very well written on a unique topic. The figures are very nice. The article is also quite timely as it integrates basic concepts in the mechanisms used by two evolutionarily divergent organisms, Toxoplasma and Chlamydia, that commonly develop within the host cell.